Negative Perception Over Widow's Status In Edith Wharton's The Age Of Innocence (1920) : A Sociological Approach - Septi Novitasari, Dwi; , Drs. M. Thoyibi, M.S; , Titis Setyabudi, S.S., M.Hum (2015)
The problem of this study is how negative perception over widow's status is reflected in Edith Wharton's The Age of Innocence. The objective of this study is to analyze the novel based on the structural elements and to analyze the novel based on the sociological approach. This study belongs to qualitative method. In this method, there are two types of data source, namely primary data and secondary data source. The primary data source is the novel with this study. The researcher collects the data from both, primary and secondary data source in a short of document as evidence. The study uses library research of descriptive analysis. Based on the analysis the researcher draws some conclusions as follows: first, in the novel, Edith Wharton disagrees if widows is a bad attitude in New York Society. Second, Edith Wharton builds her story in the novel by using social reality of American society in nineteenth century.